Indonesia Diplomacy Strategy Towards China in National Economic Resilience and Security Perspective - Pambudhi, Nurcahyo Agung; Sundari, Sri; Suwito, Suwito (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Indonesia’s economic resilience is crucial in achieving the vision of Golden Indonesia 2045, which envisions a developed nation with a strong and competitive economy. This study analyzes the Indonesia-China diplomacy strategy in strengthening Indonesia’s national economic resilience towards the Golden Indonesia 2045. Strengthening this resilience requires effective diplomacy, particularly with China, Indonesia’s largest trading partner and a significant source of foreign investment. To achieve the study’s aims, this study uses a qualitative method with a descriptive-analytical approach. This study finds that the Indonesia-China strategic partnership has flourished over the past decade, with bilateral trade reaching US78.37 billion in 2021. This partnership has extended beyond trade, encompassing infrastructure, technology, and investment cooperation, contributing positively to Indonesia’s economic indicators. However, this growing dependence also presents challenges, such as trade imbalances, necessitating a balanced and strategic approach to diplomacy. By leveraging China’s Belt and Road Initiative and other multilateral frameworks, Indonesia aims to enhance its industrial capacity, diversify exports, and attract high-value investments. This holistic approach strengthens economic resilience and positions Indonesia as a critical player in the regional and global economy, aligning with the broader goals of national development and regional stability.